PERANCANGAN ALAT PENUTUP LUKA SAAT MANDI - Triyanti, Vivi; Margana, Marco (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
When bathing, wound in human skin is likely to be exposed to water. Somehow, it would cause discomfort. The use of the wound cover (plaster, band aid, bandage) is less than satisfactory when used as taking a bath. This research will develop wound closure products in the bath, from the stage of concept development, design system level, and planning level of details. Results from trials of potential users indicate that this tool successfully met consumer needs and technical requirements which are prioritized to be developed.